Supramolecular solvent-based high-throughput sample treatment for monitoring phytohormones in plant tissues - Yonny, Melisa Evangelina (2020)
Quantification of endogenous hormones in plants is essential to understand their growth, development and response to biotic and abiotic stresses. However, it is challenging to develop high-throughput sample treatments from complex plant tissues containing low amounts of structurally unrelated and labile phytohormones while delivering clean and analyte-enriched extracts. In this paper we propose the use of supramolecular solvents (SUPRASs) made up or inverted hexagonal nanostructures of alkanols to address this challenge. The strategy was applied, as a proof of concept, to the quantification of stress-related phytohormones belonging to different categories (abscisic acid, salicylic acid, jasmonic acid, methyl jasmonate and 3-indoleacetic acid) in melon and pepper leaves. Sample treatment consisted in a single extraction-cleanup step involving the use of a low volume of SUPRAS (244 μL), the stirring (5 min) and centrifugation (15 min) of the sample at room temperature, and the direct analysis of the extract by liquid chromatography tandem mass spectrometry (LC-MS/MS). This high-throughput sample treatment method delivered excellent results for the target phytohormones regarding absolute recoveries (80–92%), method quantification limits (0.05–2 ng g−1), reproducibility (1–7%) and matrix effects (+13 to −31%), in both melon and pepper leaves, compared to reported methods based on repetitive solvent extraction, purification and solvent evaporation steps. The method was successfully applied to determine target hormones in melon and pepper plants for the evaluation of the effect of thermal stress. It was found that their concentration increased in the ranges 1.2–1.9 and 1.3–3.8 times in melon and pepper leaves, respectively, compared with control samples.